5(2x+4)+3(2x-2)=24

Simple and best practice solution for 5(2x+4)+3(2x-2)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+4)+3(2x-2)=24 equation:


Simplifying
5(2x + 4) + 3(2x + -2) = 24

Reorder the terms:
5(4 + 2x) + 3(2x + -2) = 24
(4 * 5 + 2x * 5) + 3(2x + -2) = 24
(20 + 10x) + 3(2x + -2) = 24

Reorder the terms:
20 + 10x + 3(-2 + 2x) = 24
20 + 10x + (-2 * 3 + 2x * 3) = 24
20 + 10x + (-6 + 6x) = 24

Reorder the terms:
20 + -6 + 10x + 6x = 24

Combine like terms: 20 + -6 = 14
14 + 10x + 6x = 24

Combine like terms: 10x + 6x = 16x
14 + 16x = 24

Solving
14 + 16x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 16x = 24 + -14

Combine like terms: 14 + -14 = 0
0 + 16x = 24 + -14
16x = 24 + -14

Combine like terms: 24 + -14 = 10
16x = 10

Divide each side by '16'.
x = 0.625

Simplifying
x = 0.625

See similar equations:

| x-.50x=43 | | (y+1)+1=3y | | f-g=3g | | 5(-8b-4)=180 | | 7-(-10+3x)=-238 | | y-(-3)=(8/9)(x-4) | | 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 |

Equations solver categories